2018
DOI: 10.1002/jgh3.12105
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma after direct‐acting antiviral drug treatment in patients with hepatitis C virus

Abstract: Background and Aim Given the use of direct‐acting antivirals (DAAs) to treat hepatitis C virus (HCV), their effects on hepatocarcinogenesis should be determined. Methods This study enrolled 349 patients with HCV who underwent DAA treatment at our hospital between 2014 and 2018. Their median age was 65 years, and 184 were male; 301 cases were of HCV serotype 1, and 48 were of serotype 2. The DAA treatment was daclatasvir/asunaprevir in 107 cases, sofosbuvir (SOF)/ledipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Direct acting antivirals (DAAs) introduced in 2014 have represented a revolution for the treatment of patients with HCV due to high sustained virologic response (SVR) rate (95-100% in genotype 1) and excellent tolerability [3,4]. Despite the proven SVR, there is still a risk of developing HCC that justifies careful monitoring of these patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Direct acting antivirals (DAAs) introduced in 2014 have represented a revolution for the treatment of patients with HCV due to high sustained virologic response (SVR) rate (95-100% in genotype 1) and excellent tolerability [3,4]. Despite the proven SVR, there is still a risk of developing HCC that justifies careful monitoring of these patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was found in the starting time of DAA between the HCC recurrent and nonrecurrent groups. 29 This result was supported by Degasperi et al, although HCC recurred in 7/17 (41%) patients starting DAA≤6 months from previous HCC treatment versus 13/43 (30%) patients starting DAA treatment >6 months (P=0.54), time interval between HCC treatment and DAA start could not predict HCC recurrence at univariate analysis. 30 As suggested by several studies, the early recurrence of HCC may not be related to whether to use DAA but likely to the time of DAA initiation.…”
mentioning
confidence: 54%
“…Kogiso et al confirmed that DAA did not increase the rate of HCC, even in patients who received immunosuppressive therapy in a retrospective study. 29 may reduce the second recurrence following curative treatment after the first recurrence in a landmark time analysis. 46 This finding aligned with previous results reporting that interferon treatment can reduce the second relapse but not the first relapse.…”
Section: Daa Therapy Cannot Increase the Risk Of Recurrence In Patienmentioning
confidence: 99%
“…The cause of HCC development after obtaining sustained virological response with DAA treatment is currently unknown [5]. One possible cause of HCC pathogenesis is an immunological mechanism [6]. Sustained HCV infection causes chronic inflammation in liver cells by triggering an immune response.…”
Section: Discussion/conclusionmentioning
confidence: 99%